Management and production performance of Cobb-500 broiler parent stock under open housing system (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The study was conducted to observe the management practice and production performance of Cobb-500 broiler parent strain under open housing system.  Seventy thousand Cobb-500 parent stock broiler breeder was observed for a period of 30 days. Observation was focused on   farm management including housing, feeding, watering, lighting, litter management, debeaking, deworming, vaccination, daily routine work of the farm, record keeping, bio-security and diseases control measures of Cobb-500 bird under open house  system. Results showed that the average of the body weight of Cobb-500 male birds  were 378.67g, 1599.17g, 2728g, and 4337g at starter (o to 6 weeks), grower (7 to 18 weeks), pre-breeder (19 to 23 weeks) and breeder (24 to 65 weeks) stage respectively. Similarly the average of the body weight of Cobb-500 female birds  were at starter (o to 5 weeks),  grower (6 to 18 weeks), pre-breeder (19 to 23 weeks) and breeder   (24 to 65 weeks) stage 438.5g ,1540.46g, 2247.2g, and 3479.65g respectively. The egg production at 25 weeks of age was 16.02% and peak production was 85.12 % at 35 weeks of age. The average egg production from 25 to 68 weeks of age was 60.78 %. The maximum hatchability was recorded 91.58% at 38 weeks of age. The average hatchability from 25 to 68 weeks of age was 83.93%. The above findings prove that Cobb-500 performs well under open housing system.Asian Australas. J. Biosci. Biotechnol. 2016, 1 (1), 66-72